THE COMMISSION'S LONG RUN GOALS. - Kell, Walter G. (The Accounting Review, 1958)
Since its publication in 1956, the Report of the Commission on Standards of Education and Experience for Certified Public Accountants (C.P.A.) has stimulated a tremendous amount of interest and discussion among practitioners, educators, and others. The Commission regards a college program culminating in a baccalaureate degree as a necessary preliminary to further educational training for practicing public accounting as a C.P.A. The report does not specify the content of the four year undergraduate program but it does recognize that the educational training for certified public accountants should include a substantial amount of cultural and general courses as well as the study of accounting, commercial law, finance, and other related areas of business. Moreover, graduation from a collegiate school of business is not required, but the report does stipulate that the prospective C.P.A. must either be an undergraduate accounting major or obtain the equivalent thereof subsequent to graduation.